Nonoperative Management of Splenic Trauma: An Update - Walker, John; Haq, Aftab; Suri, Rajeev (Digestive Disease Interventions, 2018)
Splenic injuries continue to be a common solid organ injury among trauma victims. Practice outcomes continue to improve with centers now routinely incorporating endovascular therapy into nonoperative management protocols. Since such incorporation, endovascular practice patterns continue to evolve as more data regarding outcomes concerning approach, embolic techniques, and time to intervention become available. These data are driving trauma centers to adopt multidisciplinary protocols with standardization of triage to nonoperative management, imaging, and endovascular interventions. This review aims to provide the interventionalist with an overview of existing and upcoming practice patterns.
Keywords: splenic trauma; nonoperative; endovascular